KEDUDUKAN HUKUM ANAK LAKI-LAKI DAN PEREMPUAN TERHADAP PEWARISAN DALAM PERKAWINAN BATAK-MINANGKABAU DI KEL. TEGAL SARI III, KEC. MEDAN AREA, KOTA MEDAN - FREDY KISWANTO (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Dr. Yefrizawati, SH, MHum2. Dr. Idha Aprilyana Sembiring, SH, MHum3. Dr. Rosnidar Sembiring, SH, MHum A marriage causes legal relation between husband and wife who yield children and between parents and their children. It can also have the impact on their joint property. A mixed marriage usually occurs in our society; for example, a marriage between a Bataknese who follows patrilineal kinship and a Minangkabaunese who follows matrilineal kinship. Inheritance for a son will be different from that for a daughter since their parents follow different types of kinship: the father is a Bataknese and the mother is a Minangkabaunese, and vice versa. This will cause dispute in the distribution of inheritance. The research problems are which inheritance adat law used in a mixed marriage between a Bataknese and a Minangkabaunese and how about the inheritance distribution for sons and daughters in the mixed marriage a Bataknese and a Minangkabaunese at Kelurahan Tegal Sari III, Medan Area Sub-district.Keywords: Inheritance Rights of Son and daughter, Mixed Marriage, Batak-Minangkabau